VALIDITAS BAHAN AJAR BERBASIS PENDEKATAN PROBLEM BASED LEARNING PADA MATERI STATISTIKA - Siti Rahmayani; Heris Hendriana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to determine how the validity of teaching materials with the Problem based learning approach is based on the results of the validation of experts. The method used in this research is the development of teaching materials according to Plomp and Nieveen which consists of 3 stages, namely initial investigation, prototyping stage and assessment stage. used in secondary schools by conducting interviews with subject teachers. At the prototype stage, the researcher compiles teaching materials which are carried out by paying attention to the steps in the Problem based learning approach. The results of this study were the development of teaching materials that were developed after a difficulty analysis was carried out through interviews with field practitioners and articles that support making researchers design learning tools that are suitable for use in accordance with expert validation. The results of the validation of the LKS worksheets obtained that the final criteria are good and are in the valid category, which means that the worksheets are suitable for use.